(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Consumption of junk foods by adolescents has become a serious public health problem. Although they are aware of the adverse health consequences, most adolescents have limited information and hence change their eating behavior minimally. Socio-economic factors, influence of peers, and availability at cheaper prices stimulate the consumption of more junk food. Cultural changes due to urbanization and adoption of Western type of food habits have enhanced this problem by shifting the food preference toward junk food consumption. Some serious physical and academic consequences of junk foods consumption include obesity, diabetes, and poor academic performance. Major challenges to improvement in eating have included a lack of access to affordable healthy food and nutrition education. To promote better eating, efforts should include school-based nutrition education along with supporting policies and community involvement. These will reduce the health risks long-term by promoting efforts in knowledge gaps and socio-economic and cultural factors. Efforts to encourage healthier food environments and policy advocacy can boost adolescent health outcome.